NILAI-NILAI RELIGIUS DALAM UPACARA MANDI BAPAPAI PADA MASYARAKAT SUKU BANJAR DI KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR - Siti Aminah; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This researcher lies behind the Tradition of bathing Bapapai conducted by the Banjar community in sub Districts Batang Tuaka. The formulation of the proplem in this study is how the Religious values contained in the bathing Bapapai ceremony to the comunity Banjar in sub Districts Batang Tuaka Regeney Indragiri Hilir. This study aims tofind out Religious values in the tradition of bathing Bapapai in sub Districts Batang Tuaka. This research conducted in sub Districts Batang Tuaka in January 2018 until June 2018. This research is a qualitative descriptive which onformants in thisstudy are informants selected purposively as needed and combined with snowbowling techniques. As for the informants studied are as follows : figures Bapapai, community leaders, and the community Batang Tuaka. Using data collection techniques : observation, interviews, documentation methonds with triangulatioan techniques. Using data analysis techniques : data collection, reduction, data presentation, conclusions and verification. Based on the results of the study indicate that there are religious values of the five values namely, the value of worship, the value of the spirit of jihad, moral values and discipline, exemplary values, and the values of trust and sincerity. Contained in the tradion of bathing Bapapai in sub Districts Batang Tuaka Regeney Indragiri Hilir. Trus the hypothesis that says there are religious values contained in the tradition of bathing Bapapai in sub Districts Batang Tuaka Regeney Indragiri Hilir.Keywords: Religious Values, Bathing Tradition Bapapai Banjar community Batang Tuaka.